The Communists and the Roman Catholic Church in Yugoslavia, 1941-1946 - Palmer, P; Palmer, Peter (2000)
﻿ This thesis examines the development of the Yugoslav Communists' approach towards the Catholic Church during the period of their takeover and consolidation of power from the outbreak of war in April 1941 until late 1946. In recent years, a comprehensive reappraisal of the Communist takeover has been going on in the countries of former Yugoslavia, and this work draws on this new scholarship, as well as on hitherto unused archival material. It examines the development of the Communists' popular front line during the war, according to which the Communist-dominated Partisan movement sought to appeal to non-communists, including Catholics, to join them in ousting the occupier. As such, this policy meant downplaying the Communists' revolutionary programme, which they never actually gave up. The thesis examines in detail the application of the popular front policy among the Catholic Croats of Croatia and Bosnia, and among the Slovenes. It describes how the Communists avoided actions or pronouncements that would have offended the Church, attempted to have cordial relations with the Church hierarchy and encouraged the active participation of Catholic clergy and prominent lay people in the movement. The prime purpose of this was to reassure the Catholic population that they had nothing to fear from a Communist takeover. However, the hostility between the two sides was not overcome, as revealed in the violence of the Communists towards many of the clergy during the period immediately before and after their takeover. Following this, the Communists' implementation of their revolutionary programme brought them into direct conflict with the interests of the Church, especially in their curtailing of the role of the Church in education and in their confiscation of Church property. Relations quickly degenerated into open confrontation, as the Church could not accept the limited role in society which the Communists were prepared to grant it.